2019
DOI: 10.1007/s00181-019-01694-5
|View full text |Cite
|
Sign up to set email alerts
|

Does business confidence matter for investment?

Abstract: Business confidence is a well-known leading indicator of future output. Whether it has information about future investment is, however, unclear. We determine how informative business confidence is for investment growth independently of other variables using US business confidence survey data for 1955Q1-2016Q4. Our main findings are: (i) business confidence leads US business investment growth by one quarter, and structures investment by two quarters; (ii) business confidence has predictive ability for investmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
2
22
0
1
Order By: Relevance
“…Such models can include several hundred and even thousands of variables and equations, often having interdependent variables. Thus, for analysing the business confidence predictive ability for investment growth, Khan and Upadhayaya (2019) have used structural dependencies and found that business confidence leads US business investment growth, and structures investment, as well as exogenous shifts in business confidence, reflect short-lived non-fundamental factors, consistent with the 'animal spirits' view of investment.…”
Section: Conceptual Background and Hypotheses Developmentmentioning
confidence: 99%
“…Such models can include several hundred and even thousands of variables and equations, often having interdependent variables. Thus, for analysing the business confidence predictive ability for investment growth, Khan and Upadhayaya (2019) have used structural dependencies and found that business confidence leads US business investment growth, and structures investment, as well as exogenous shifts in business confidence, reflect short-lived non-fundamental factors, consistent with the 'animal spirits' view of investment.…”
Section: Conceptual Background and Hypotheses Developmentmentioning
confidence: 99%
“…They used US business confidence survey data between 1955Q1-2016Q4 and found that Business Confidence has predictive power for investment growth. Compared to traditional forecasting indicators, Business Confidence has a stronger ability to predict investment downturns in the first three quarters and signs of investment growth in the second quarter [27].…”
Section: The Analyze Of the Correlation Between Economic Standards Anmentioning
confidence: 94%
“…The relationship between business confidence (or business sentiment) and economic variables has been analyzed in the literature (e.g., business confidence and stock prices [Darling 1955]; business confidence and investment [Khan and Upadhayaya 2019]; business confidence and economic activities [Taylor and McNabb 2007; de Mendonça and de Oliveira 2019]; business confidence and industrial production [Bruno, Crosilla, and Margani 2019]). However, very few studies have examined the link between business confidence and tourism-related variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Milani (2017) find that more than 40% of historical US business cycle fluctuations are explained by business and consumer sentiment shocks. In terms of investment, Khan and Upadhayaya (2019) show that business confidence has predictive ability for investment growth in the United States between 1955 and 2016.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation